2001
DOI: 10.1159/000054634
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Alters γ-Aminobutyric Acid Neuronal Activity in the Hypothalamus and Cerebral Cortex in the Rat

Abstract: γ-Aminobutyric acid (GABA) neurons terminating in the hypothalamus have been implicated in the neuroendocrine regulation of reproductive hormones, particularly luteinizing hormone (LH) and prolactin. The aim of this study was to examine whether GABAergic neuronal activity in the hypothalamus was modified during lactation, and whether any observed changes correlated with changes in secretion of these hormones. Animals were divided into three experimental groups: diestrous controls, lactating with pups present (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
3
16
0
1
Order By: Relevance
“…Previous studies have reported on an increased level of GABA in distinct regions of the maternal brain (Kornblatt and Grattan, 2001; Rodriguez et al, 2004). Consistent with these observations, our recent work found upregulated Gad1 and Gad2 expression in the postpartum LS (Zhao et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on an increased level of GABA in distinct regions of the maternal brain (Kornblatt and Grattan, 2001; Rodriguez et al, 2004). Consistent with these observations, our recent work found upregulated Gad1 and Gad2 expression in the postpartum LS (Zhao et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma progesterone and leutinizing hormone (LH) levels were measured using standard radioimmunoassays described in the literature (Trawick and Bahr, 1986;Kornblatt and Grattan 2001) by the Yerkes Neuroendocrine Laboratory.…”
Section: General Methodsmentioning
confidence: 99%
“…*Corresponding Author: Grace Lee, Address: 1117 W. Johnson St., University of Wisconsin, Madison,WI 53706,Email: glee1@wisc.edu,Telephone: (608) Fax: (608) 262-9083.Previous studies have identified altered neurotransmission of gamma-aminobutyric acid (GABA), the principle inhibitory neurotransmitter in the central nervous system (CNS), as supporting maternal physiology and behavior. For example, in the supraoptic nucleus (SON), there is increased clustering of GABA A receptors (Koksma et al, 2005), increased GABAergic synapses (El Majdoubi et al, 1997;Gies and Theodosis, 1994;Kornblatt and Grattan, 2001;Theodosis et al, 1995;Theodosis and Poulain, 2001) and increased GABA release onto oxytocin neurons (de Kock et al, 2003) in lactating versus non-lactating females. Additional brain regions, including the medial preoptic area (MPA) (Kendrick et al, 1992), the bed nucleus of the accessory olfactory tract (BAOT) (Rodriguez et al, 2004), the cingulated cortex (Cg) (Kornblatt and Grattan, 2001), and other hypothalamic areas (Kornblatt and Grattan, 2001), also exhibit altered GABAergic transmission with lactation.…”
Section: Introductionmentioning
confidence: 99%